ANALISIS KEPUTUSAN PETANI MENJUAL KELAPA DALAM BENTUK KELAPA MUDA DI DESA BANDAEHA KECAMATAN MOLAWE KABUPATEN KONAWE UTARA - Resky Ardiansyah; Mardin Mardin; La Ode Kasno Arif (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2025)
Bandeha Village, a region with a high coconut production rate, is developing coconut farming amidst the potential for coconut processing into copra, oil, and other products. Conversely, coconut farmers in Bandaeha Village prefer to sell young coconuts, citing various considerations to increase coconut farming yields. This study aims to determine the factors influencing farmers' decisions to sell young coconuts in Bandaeha Village, Molawe District, North Konawe Regency. The informants in this study were all five coconut farmers who sell their harvest as young coconuts in Bandaeha Village. The method used in this study was qualitative analysis, with data collection through interviews, observation, and documentation. The results indicate five main factors influencing farmers' decisions to sell young coconuts in Bandaeha Village, Molawe District, North Konawe Regency: market demand, faster harvest time, lower maintenance costs, climate and weather conditions, and short-term capital needs.